The content of some available heavy metals in chernozems from Ovche Pole - Petkovski, Dime; Melovski, Ljupčo (Macedonian Journal of Ecology and Environment, 1995)
This study represents the results of the investigation of some heavy metals (Mn, Fe, Cu, Zn, Co and Pb) content (easy soluble) in the chernozem soils from Ovche Pole. The soil samples were collected in October 1995 representing the horizons Ap, A, AC, C of chernozems from OPO of Agricultural Institute - Skopje in Amzibegovo - Ovche Pole. An average samples from 0-20 cm and 20-40 cm depth were also collected. Beside the heavy metal content, some physical parameters and other common chemical properties of the soil were estimated as well. The content of easy soluble heavy metals in the investigated soils is mainly due to the natural weathering of primary rock minerals, and not to the anthropogenic pollution, especialy concerning the lead content.